Information Management Behaviour of Rice Farmers under Collective Farming in Kerala - Anwar, Anusha; Rambabu, P; Gopi Krishna, T (Journal of Extension Education, 2018)
The study was conducted in Kannur district of Kerala State, to assess the information management behaviour of rice farmers under the collective farming project of Kudumbashree mission. Expost facto research design was followed for the study. A sample of 120 farmers was selected by using proportionate sampling procedure and information was gathered and analyzed. The results showed that majority of the women rice farmers belonged to medium category of information management behavior.